Intercultural citizenship in the (foreign) language classroom - Porto, Melina (2017)
The purpose of this special issue is to bring the theory of intercultural citizenship education to readers’ attention and to offer teachers and researchers working with this or similar concepts the opportunity to make their work known in a context of a coherent presentation of theory and practice. In this introduction, we will explain the rationale and the concepts involved in intercultural citizenship education and present the articles in this special issue which arose from our call for papers.